ANALISIS JARINGAN KOMPUTER LABORATORIUM FAKULTAS ILMU KOMPUTER UNIVERSITAS KATOLIK SANTO THOMAS MEDAN - barutu, Serliana; Kartika Simbolon, Leni; Insani Berasa, Yustri; Abelisa Manalu, Michele (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2025)
The aim of this study is to evaluate the performance of the computer network in one of the organization’s labs of the Faculty of Computer Science at Universitas Katolik Santo Thomas by measuring important network metrics such throughput, latency, packet loss, and jitter. Using a quantitative methodology with tools like iPerf, the testing was carried out at peak hours on five computers connected to the local network. The findings indicate that all parameters are in the excellent range, with the exception of jitter, which saw modest drop from the prior investigation. In contrast to earlier studies conducted at the faculty wide level, this one recorded improvements in throughput and packet loss indicators, while latency remained constant and jitter somewhat decreased. These results demonstrate a considerable advance in the performance of the local network, demonstrating increased efficiency and dependability. It is expected that the findings of this research will help to improve network infrastructure planning and maintenance in academic institutions.